2013
DOI: 10.1016/j.jagp.2013.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Are Apathy and Depression Independently Associated with Longitudinal Trajectories of Cortical Atrophy in Mild Cognitive Impairment?

Abstract: Objective We sought to examine whether depression and apathy are independently associated with longitudinal trajectories of cortical atrophy in entorhinal cortex compared to frontal subregions previously implicated in late-life mood disturbance. Design Data from 334 participants classified as having Mild Cognitive Impairment (MCI) in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) were analyzed using multilevel models for change adjusted for age, global cognitive status, and total intracranial volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 40 publications
(46 reference statements)
5
49
1
Order By: Relevance
“…It has been suggested that changes in the serotonergic system driven by neurodegeneration in adjacent cholinergic system may induce depression and accelerate cognitive impairment (32). Thus, our findings could also be explained by a progression of the underlying MCI neurodegenerative pathology, as previously suggested (16, 17). We cannot exclude, however, yet another explanation, namely that chrDS in MCI may represent an atypical neurodegenerative pattern with additional frontal and ACC atrophy, a line of thought supported by studies of atypical AD (33).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been suggested that changes in the serotonergic system driven by neurodegeneration in adjacent cholinergic system may induce depression and accelerate cognitive impairment (32). Thus, our findings could also be explained by a progression of the underlying MCI neurodegenerative pathology, as previously suggested (16, 17). We cannot exclude, however, yet another explanation, namely that chrDS in MCI may represent an atypical neurodegenerative pattern with additional frontal and ACC atrophy, a line of thought supported by studies of atypical AD (33).…”
Section: Discussionsupporting
confidence: 82%
“…In a study of depressive symptoms assessed at baseline in relation to longitudinal brain changes in MCI, depressive symptoms were associated with accelerated cortical atrophy in ACC (16). A more recent study in MCI found that chronic, but not baseline depressive symptoms were associated with bilateral frontoparietotemporal white matter (WM) atrophy and consequently with an increased risk to develop AD (17).…”
Section: Introductionmentioning
confidence: 99%
“…Mendez et al, for example, verified a correlation between anxiety and dysthymia with hypoperfusion of the right temporal lobe 13 . Other studies have also examined the correlation between depression and a reduction in cortical thickness on the entorhinal cortex and the anterior cingulated cortex 14 . Because of these findings, it is possible to note the relevance of correlations between affective syndrome and the frontal and temporal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…7,55 Both dopaminergic denervation and cholinergic abnormalities aff ect the lateral and medial regions of the prefrontal cortex in Parkinson's disease. Degeneration of mesencephalic dopaminergic neurons at Braak stage III of the disease leads to dopamine depletion in the mesocortical and mesolimbic systems, 56 and the spread of synucleinopathy to subcortical and cortical dopamine projection areas further impairs their functionality during Braak stages IV and V. 57,58 Delineation of the diff erent components that can lead to apathy is crucial to the planning of therapeutic strategies.…”
Section: Reviewmentioning
confidence: 99%